Pelatihan Strategi Koping Pada Remaja di SMAN 1 dan SMKN 2 Sukawati Kabupaten Gianyar Tahun 2018 - I Nengah Sumirta (Jurnal Pengabmas Masyarakat Sehat, 2019)
Teenagers is of a transition period with various changes either physical, psikososial and spiritual. Teenagers have not been able to meguasai or control maximally physical function and psikososialnya so that various problem was due to developments as use of alcohol , premarital sex , behavior violence, drug use, pregnancy does not desired , etc .This situation peru received the attention of various parties. The purpose of this activity is give the ability to youth to choose a koping effective in solving the problems faced by, so that they become adolescent that is tough and not a quitter when faced with particularly difficult a problem .Methods used is training , the targets were a sman 1 and smkn 2 sukawati kabupaten gianyar, were 40 people .Results showing that teenagers before it was given training srategi koping, teenagers greater use of emotional focused coping namely 27 people ( 67,5 % ). The capability of teenagers having given training in koping choose a most effective to deal with in life sehari-hari .From the statistical analysis indicated the p = 0,000 classifiable focused either on coping or emotional focused coping.Keyword: Adolescent, Coping Strategy.